Algorithm for Transmission Parameters Selection for Sporadic URLLC Traffic in Uplink - Shashin, A. E.; Belogaev, A. A.; Krasilov, A. N.; Khorov, E. M. (Journal of communications technology & electronics, 2022)
Ultra-Reliable Low-Latency Communications (URLLC) is a key service for fifth generation (5G) cellular systems. Typical requirements for this service are transmission reliability above 99.999% and latency below 1 ms. The paper considers a scenario with sporadic URLLC traffic in the uplink. To satisfy the strict latency requirements, user equipments (UEs) use the grant-free channel access method. According to this method, the base station allocates time–frequency resources and selects transmission parameters (i.e., the modulation and coding scheme, number of transmission attempts) in advance for each UE. To provide high resource utilization in the case of sporadic traffic, the base station allocates shared channel resources to several UEs, which can lead to interference between transmissions of different UEs. The paper proposes an algorithm for selection of transmission parameters for each UE that takes into account the channel conditions of each considered UE and the interference caused by transmissions of other UEs. Numerical results obtained with NS-3 show that the proposed algorithm increases the network capacity up to six times with respect to the algorithms presented in the literature.